The Role of Merchandisers in Enhancing Business Performance in the Pharmaceutical Industry - Artanaya, I Komang; Mulyani, Dwi; Djastuti, Indi; Perdhana, Mirwan Surya (Research Horizon, 2024)
The sustainability of a pharmaceutical company is determined, in part, by how well its products are known and subsequently purchased by consumers, both loyal and new. In this regard, the role of the Merchandiser Display (MD) in carrying out AVP activities (Availability, Visibility, and Predictability) for products is highly central and strategic. The objective of this article is to understand the strategic importance of the MD's role in enhancing sales through merchandising activities. We employed a qualitative research method involving direct non-participant observation, documentation, and interviews with the Head of Area (HOA) and Team Leader (TL) overseeing 100 MDs from three different pharmaceutical companies in Indonesia. The research findings and discussions revealed that MDs play a strategic role in increasing sales through close monitoring of AVP products, which results in impulse buying and perceived quality. The research results contribute to and benefit pharmaceutical companies by maximizing the role of MDs as a crucial factor in optimizing sales performance and maintaining the company's sustainability.